Ameliorative effects of aqueous seed-extract of Dacryodes edulis on doxorubicin-induced cardiac tissue damage in albino rats - Matthias C. Ominyi; Augustine A. Uwakwe; Friday N. Nweke; Fedrick U. Ali; Moses E. Ogbanshi; Lilian N. Ebenyi; Victor U. Nwankwo; Emmanuel O. Ogueji (Kuwait Journal of Science)
Ameliorative effects of aqueous seed-extract of Dacryodes edulis on doxorubicin-induced cardiac tissue damage in albino rats were investigated. The animals were divided into groups and fed for 14 days to acclimatize. Single dose of 15 mg/kg body weight doxorubicin was given intraperitoneally to all the groups except control. After 48 hours, two animals were randomly selected from each group and sacrificed under ethyl-ether anesthesia, to harvest their hearts for histological studies. Groups 1 and 2 were given normal saline, while groups 3 and 4 were treated with 25 and 100 mg/kg body weight of aspirin and vitamin C. Groups 5-8 received different doses of aqueous seed-extract (200, 400, 600 and 800 mg/kg body weight). Treatments lasted for 21 days and the rats were sacrificed under anesthesia, and their hearts harvested and fixed in formol saline for examination. The photomicrograph revealed severe and focal loss of cardiac fibre, intra-myocardial hemorrhages, and fragmentation of cardiac muscle and disorganization of histoarchitecture in the induced but untreated animal groups. Micrographs showed significant ameliorative effects of the extract in dose-dependent way and healing effects of the standard drugs. These results showed that aqueous seed-extract of Dacryodes edulis exhibits therapeutic potentials for cardiac disorders.